INTERACTION OF A SURFACE SOLITARY WAVE WITH SUBMERGED AND SEMI-SUBMERGED BREAKWATERS - Gorban, I. M.; Korolova, A. S.; Lebid, O. G. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2022)
The interaction of a surface solitary wave with a semi-submerged curtain wall and an underwater barrier was experimentally investigated. The incident wave amplitude, the draft of the semi-submerged wall and the height of the submerged barrier were varied in different experiments to derive the most effective breakwater configurationin terms of reflection and transmission wave coefficients. It was obtained that the meeting of a solitary wave with the curtain wall looks as follows: the reflected wave is formed from the roll of the incident wave on the structure, and the transmitted wave grows after the passage of the liquid mass through the gap between the bottom and the lower part of the wall. The interaction of a solitary wave with a submerged barrier depends on the ratio of the incident wave amplitude to the thickness of the water column above the obstacle. When its value is less than a critical value, which is about 1, the incident wave splits smoothly into reflected and transmitted solitons. Otherwise, intense chaotic oscillations of the free surface occur above the obstacle. Evaluations of wave reflection and transmission coefficients showed that thin vertical barriers are sufficiently effective in reducing the intensity of nonlinear solitary waves. The target protection can be achieved by choosing the best draft of the impervious part of the curtain wall or the optimal height of the submerged barrier. A semi-submerged wall was shown to be more effective for damping the energy of a solitary wave compared to an underwater barrier installed on the bottom. The curtain wall can dissipate up to 60% of the energy of the incident wave, while the submerged barrier - up to 20%.